2019
DOI: 10.3390/molecules24122211
|View full text |Cite
|
Sign up to set email alerts
|

Current Aspects of siRNA Bioconjugate for In Vitro and In Vivo Delivery

Abstract: Studies on siRNA delivery have seen intense growth in the past decades since siRNA has emerged as a new class of gene therapeutics for the treatment of various diseases. siRNA bioconjugate, as one of the major delivery strategies, offers the potential to enhance and broaden pharmacological properties of siRNA, while minimizing the heterogeneity and stability-correlated toxicology. This review summarizes the recent developments of siRNA bioconjugate, including the conjugation with antibody, peptide, aptamer, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 136 publications
(183 reference statements)
0
51
0
Order By: Relevance
“…The exact mechanisms of how amphiphilic modification leads to subcellular organelle accumulation remain poorly established, but it is believed that the overall physicochemical properties and ligand–receptor interactions govern the intracellular sorting and trafficking pathways . For example, amphiphilic modification is an effective way for cytosolic targeting of small interfering RNAs (siRNA) . Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non‐endocytotic pathway mediated by the scavenger receptor BI .…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of how amphiphilic modification leads to subcellular organelle accumulation remain poorly established, but it is believed that the overall physicochemical properties and ligand–receptor interactions govern the intracellular sorting and trafficking pathways . For example, amphiphilic modification is an effective way for cytosolic targeting of small interfering RNAs (siRNA) . Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non‐endocytotic pathway mediated by the scavenger receptor BI .…”
Section: The Design Principles Of Self‐delivery Amphiphilic Drugsmentioning
confidence: 99%
“…[82] For example, amphiphilic modification is an effective way for cytosolic targeting of small interfering RNAs (siRNA). [21,[84][85][86] Lipophilic ligands modified siRNA associate with high density lipoproteins and cross the membrane directly into cytoplasm via non-endocytotic pathway mediated by the scavenger receptor BI. [87] A wide range of lipophilic moieties including cholesterol, fatty acids, and steroids were used for siRNA conjugation and some of them have reached clinical stage.…”
Section: Amphiphilic Modification Facilitates Drug Uptake and Targetimentioning
confidence: 99%
“…The siRNA is a negatively charged molecule, and it is almost impossible for siRNA to cross the biological membrane. The half-life of most naked or unmodified siRNA is between 5–10 min [ 46 ]. Table 2 illustrates the barriers faced by siRNA to reach its site of action.…”
Section: Barriers To Sirna Deliverymentioning
confidence: 99%
“…Conjugation with polymer, especially PEG, is a common concept to increase the half-life of siRNA in blood and enhance the pharmacokinetic profiles [ 46 , 75 ]. A study demonstrated that conjugating siRNA with 20k PEG resulted in a slower rate of renal clearance (50% remained 1 h after injection) as compared to unmodified siRNA (<10% remained 15 min after injection) [ 76 ].…”
Section: Intravascular Degradation and Renal Clearancementioning
confidence: 99%
“…However, the efficient delivery of siRNAs to their targeting cell is still one of the significant limitations of this strategy because siRNAs could be degraded by extracellular nucleases present in host tissues [ 94 , 95 ]. Therefore, new strategies have been developed to improve siRNAs’ delivery, including different conjugation methods with immunoproteins, peptide ligands, or aptamers [ 95 , 96 , 97 ]. Besides, siRNAs could also be encapsulated in gold or silver-based nanoparticles, liposomes, or cyclodextrin complexes that may protect their cargo against nuclease attacks [ 95 , 96 , 97 ].…”
Section: Other Alternative Anti-infectives Against Staphylococcimentioning
confidence: 99%